1989
DOI: 10.1161/01.res.65.2.237
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic constriction in the general circulation and its role in coronary artery spasm.

Abstract: The release of acetylchoUne from autonomic nerves in those tissues that receive a cholinergic innervation is widely believed to dilate blood vessels. Exogenously administered acetylchoUne hi vivo does dilate vascular beds and produce hypotension; however, this latter effect is indirect and probably the result of liberation of endothelium-derived relaxing factor (EDRF) from endothelial cells. Some blood vessels contain a substantial population of medial constrictor receptors for acetylchoUne, and the implicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
42
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 147 publications
(61 reference statements)
2
42
3
Order By: Relevance
“…This vasoconstriction was abolished by atropine, and thus is muscarinic receptor mediated. In support of our findings, recent studies have shown that ACh contracts large coronary arteries isolated from adult pigs (5) and humans (6). The mechanism by which ACh causes this vasoconstriction , however, has not been delineated.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This vasoconstriction was abolished by atropine, and thus is muscarinic receptor mediated. In support of our findings, recent studies have shown that ACh contracts large coronary arteries isolated from adult pigs (5) and humans (6). The mechanism by which ACh causes this vasoconstriction , however, has not been delineated.…”
Section: Discussionsupporting
confidence: 83%
“…Our hearts were perfused at constant coronary flow, and thus it is unlikely that vasoconstriction impaired myocardial oxygen delivery. Nevertheless, coronary vasoconstriction to ACh may be heterogenous (6,21), e.g. in regard to responses in epicardial versus endocardial vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wilde et al (21) mentioned that thiamine deficiency can lead to ST-segment elevation in the right precordial leads. Previous studies have demonstrated that various central and autonomic nervous system abnormalities can result in ST-segment elevation with or without CK elevation (22)(23)(24)(25)(26)(27). The autonomic nervous function also participates in the formation of Brugadatype ECG (28,29), and unbalanced autonomic nerve function has been thought to play an important role in inducing Brugada-type ECG (30).…”
Section: Discussionmentioning
confidence: 99%
“…Contraction has also been reported in the pulmonary vessels of rabbits (Altiere et al, 1986) and in coronary arteries of most species (Kalsner, 1989), with thromboxane A 2 being the putative Mediator since constriction could he prevented by cyclooxygenase inhibitors, thromboxane A 2 synthase inhibitors and thromboxane A 2 antagonists (Altiere ., 1986). In addition, our findings seem to exclude an important role for prostaeyclin, another endothelium-derived relaxing factor, in the ACh-induced relaxation of guinea pig pulmonary arteries.…”
Section: Discussionmentioning
confidence: 88%